Standardization of processing parameters for production of protein hydrolysate from chicken liver by using Lactobacilli fermentation: Protein hydrolysates from chicken liver - Bora, Bedika; Kumar, Devendra; Biswas, Ashim Kumar; C K, Faslu Rahman; T S, Anand (Indian Journal of Poultry Science, 2025)
This study aimed to optimize fermentation conditions for producing chicken liver hydrolysates with antioxidant properties using Lactobacilli, contributing to a more sustainable and resilient food and poultry industry. Chicken liver protein hydrolysates were prepared by fermentation using Lactobacillus helveticus and Lactiplantibacillus plantarum, and their concentrations and processing conditions were optimized according to pH and degree of hydrolysis. SDS-PAGE was performed to evaluate molecular weight of hydrolysates and then antioxidant activity was assessed. Two hydrolysates showing best antioxidant activities were selected for further physico-chemical characterization after freeze drying. The SDS-PAGE analysis of liver protein hydrolysates obtained by L. helveticus fermentation showed bands in range of 15-5 kDa, whereas those obtained by L. plantarum fermentation showed distinct bands in the range of 18-5 kDa. Hydrolysates fermented with a 2% inoculation rate for 16 hours exhibited a significantly (p<0.05) higher degree of hydrolysis, as well as increased DPPH and ABTS values, before undergoing freeze-drying. The freeze-dried hydrolysates fermented with L. helveticus demonstrated a significantly (p<0.05) higher yield and protein content. These findings conclude that Lactobacilli fermentation can be used effectively for the production of chicken liver hydrolysates with bioactivities such as antioxidant properties and effectively used in the food industry.